Synthesis of Biphenyl- 4,4'-Diyl bis(phenyl-methanone) via Carbonylative Coupling - Lee, Do-Hun; Hahn, Jung-Tai; Jung, Dai-Il (Asian Journal of Chemistry, 2013)
Luminescent meterials have a major technological role for human kind in the form of application such as organic and inorganic light emitters for flat panel and flexible displays such as plasma displays, LCD displays and OLED displays. To develop a luminescent material with high colour purity, luminous efficiency and stability, we synthesized diketone by carbonylative Suzuki coupling in the presence of Pd(NHC) (NHC = N-heterocyclic carbene) complex as the catalyst. Carbonylative coupling of 4,42-diiodobiphenyl and phenylboronic acid was investigated to study in detail the catalytic ability of the Pd(NHC) complex. Reactions were carried out using both CO and metal carbonyls. Bis-(1,3-dihydro-1,3-dimethyl-2H-imidazol-2-ylidene) diiodo palladium was used as the catalytic complex. Reaction products biphenyl-4,4'-diyl bis(phenyl methanone) 3 and (4'-iodobiphenyl-4-yl)(phenyl)methanone 4 were obtained as a result of CO insertion into the palladium(II)-aryl bond. However, when pyridine-4-yl boronic acid was used in place of phenylboronic acid as the starting reagent, synthetic reaction yielding 3 and 4 were found not to occur.